Becoming with the dog in South Africa Reflections on family, memory, and human-animal relations in post-apartheid South Africa - Ndaba, Mpho Antoon (Department of English Language and Literature, 2023)
Can the relationship White people have with the figure of the dog, in what currently exists as South Africa, be free of antiblackness? Following instances where I saw black women who worked as domestic workers walk dogs belonging to their White employers, I write these letters addressed to you, my sister, Palesa – meditating on the dog-Human relationships as sites of racial violence. The core analytic framework and theory I employ to explore these extreme, mundane, and in-between forms of violence, is Afro-Pessimism.